DEVELOPMENT OF AN ENGLISH VOCABULARY POCKET BOOK FOR BUILDING INFORMATION MODELING DESIGN STUDENTS - Agati sri haryati; Harahap, Anna leli; Rizki Lestari (Journal of English Education and Linguistics, 2026)
This research aims to describe the development process, assess the validity, and evaluate the effectiveness of an English vocabulary pocket book designed as a supplementary learning medium for students of the Building Information Modeling Design Department at SMK Negeri 2 Rantau Utara. Conducted from February to March 2025, the study employed the ADDIE model, encompassing five phases: Analysis, Design, Development, Implementation, and Evaluation. The research involved 35 Grade XI students as participants. Data were gathered through interviews, validation sheets, and pre-test and post-test instruments. The developed pocket book was validated by media and material experts, achieving high feasibility scores of 92.2% and 91.4%, respectively. The results of the pre-test and post-test showed an improvement in students’ vocabulary acquisition, with average scores increasing from 65.8 to 71.3. These findings suggest that the pocket book is a valid, practical, and effective tool to support vocabulary learning in vocational education